2018
DOI: 10.18203/2394-6040.ijcmph20180238
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of burn cases admitted to a tertiary care centre of Odisha

Abstract: Background: India, has an estimated annual incidence of 6-7 million burn cases. In the state of Odisha, there are very few epidemiological studies of Burn injuries. Therefore a hospital based descriptive study among the admitted burn cases was conducted. Methods: The study was conducted among the burn cases admitted to the burn unit of Surgery Department of SCB Medical College and Hospital, Cuttack during the time period from 1st January 2014 to 31st May 2015.A total of 145 patients were included for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In our study, 78% burn cases were married. Similar findings were seen in a study conducted by Singh A et al [25] 76.8%, Ghaffar [28] 72.5%, Panda et al [29] 78%, Bhatt et al [14] 75.4%, Dasari et al [6] 82.6%. Females physical and psychological stress of marriage, harassment by parents-in-law or dowry harassment was observed.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, 78% burn cases were married. Similar findings were seen in a study conducted by Singh A et al [25] 76.8%, Ghaffar [28] 72.5%, Panda et al [29] 78%, Bhatt et al [14] 75.4%, Dasari et al [6] 82.6%. Females physical and psychological stress of marriage, harassment by parents-in-law or dowry harassment was observed.…”
Section: Discussionsupporting
confidence: 88%
“…The mean age of the people who had suffered burn injury in our study was also quite similar to the other studies. 6,7 This study revealed that the majority of burn injuries occurred inside the house, which goes along with the systemic review done by Tripathee et al 8 Scald burn injury was the commonest mode of injury followed by flame burn injury in this study, which is a bit different that other previous studies that showed flame burn as the commonest mode of injury 3,5 . This difference might be due to different socio-environment condition of the samples and small size of the study population.…”
Section: Discussionmentioning
confidence: 37%
“…In the present study, burn injury was slightly more common in females than in males which is quite similar to other studies. [3][4][5][6] This might be because females are mostly involved in the household activities and household activities like cooking are the main culprit of burn injury in our scenario. The mean age of the people who had suffered burn injury in our study was also quite similar to the other studies.…”
Section: Discussionmentioning
confidence: 98%
“…The age range of 18 to 30 years produced the most donors; in the current study and past reports, a tendency of this nature was seen. Additionally, given the low number of female donors identified by the present study, efforts should be undertaken to boost the number of female donors [ 12 - 14 ]. Several developed nations have outlawed the use of paid blood donors to lessen the risk of diseases transferred through transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the percentage prevalence of HBV, HCV, and HIV in India among blood donors reduced from 1.62%, 1.85%, and 1.16% (in 2004) to 0.92%, 0.52%, and 0.21% (in 2009), respectively. The prevalence of these viral infections decreased significantly in our neighboring countries in recent years [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%